2020
DOI: 10.1080/21681805.2020.1732463
|View full text |Cite
|
Sign up to set email alerts
|

Non-metastatic prostate cancer: rationale for conservative treatment and impact on disease-related morbidity and mortality in the elderly

Abstract: Purpose: To determine the rationale for not offering local treatment to prostate cancer patients with non-metastatic disease at diagnosis who later died of prostate cancer and to document local and systemic complications caused by disease progression. Material and Methods: In this population-based, retrospective study we reviewed the medical records of all patients who died of prostate cancer in 2009-2014 in Vestfold County (Vestfold Mortality Study), who were non-metastatic at diagnosis and who had received n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Similar to younger men, senior adults in the NoCurTrt group had a twofold increased risk of overall death within five years of diagnosis compared to patients treated curatively. The considerable 5‐year PCSM rates, along with the high proportion of patients having ISUP grade group ≥ 4 tumors and ECOG status ≤ 1 in the NoCurTrt group, suggest the likelihood of undertreatment, as also emphasized in other studies 27,4026 …”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Similar to younger men, senior adults in the NoCurTrt group had a twofold increased risk of overall death within five years of diagnosis compared to patients treated curatively. The considerable 5‐year PCSM rates, along with the high proportion of patients having ISUP grade group ≥ 4 tumors and ECOG status ≤ 1 in the NoCurTrt group, suggest the likelihood of undertreatment, as also emphasized in other studies 27,4026 …”
Section: Discussionmentioning
confidence: 60%
“…Any life‐prolonging effect from CurTrt must in these patients be weighed against the risk of adverse treatment‐related effects and death from other causes than PCa 19‐21 . Studies have indicated that treatment decisions in PCa patients are primarily based on chronological age rather than biological age 7,22‐27 . Undertreatment of healthy senior adults with high‐risk PCa may thus contribute to the described high incidence of death from PCa in the elderly population 5,6,20,21 …”
Section: Introductionmentioning
confidence: 99%
“…Older patients with cancer tend to perceive HRQoL as more important than improved survival compared to younger patients [20,21]. However, lack of tumour control could increase symptom burden and require surgical and medical interventions [2]; thus, immediate tumour‐directed treatment, could confer long‐term HRQoL benefits.…”
Section: Discussionmentioning
confidence: 99%
“…With the development and progress of modern medical technology, the cure rate of the disease is increasing, and most patients with prostate cancer will receive compound kushen injection for comprehensive endocrine treatment in order to control the number of tumor cells, improve clinical symptoms, enhance the quality of life, and prolongsurvival time. However, the psychological changes of patients are often ignored in practice, and adverse psychological emotions or inadequate family support will also have a negative impact on the treatment effect of patients, leading to unsatisfactory results of compound kushen injection [17][18][19][20]. With the advancement of medicine, more attention has been paid to the psychological recovery of patients, especially in elderly patients with prostate cancer.…”
Section: Discussionmentioning
confidence: 99%